Monofloral honeys by Sicilian black honeybee (Apis mellifera ssp. sicula) have high reducing power and antioxidant capacity. Issue 11 (November 2016) - Attanzio, Alessandro; Tesoriere, Luisa; Allegra, Mario; Livrea, Maria A.
Abstract: Thirty samples from thirteen Sicilian monofloral honeys by the local black honeybee, and two honeydew honeys, were studied to assess phenol content, reducing power and antioxidant capacity as well as correlations among these parameters. Honeys from Apiaceae showed the highest phenol amount and capacity to reduce ferric ion and stable chemical radicals, whereas honeys from Leguminosae the lowest. All honeys were active against myoglobin-derived radicals usually formed in red meat after storage and/or heating and significant correlation ( p = 0.023) was found between flavonoid content and deactivation rate of this radical. Dill > almond > tangerine > thistle > sulla honeys inhibited formation of lipoperoxides in either iron/ascorbate or azoinitiator -induced membrane lipid oxidation, whereas eucalyptus honey was mostly effective in the metal-dependent model. Honeys by black honeybee possess remarkable reducing power and antioxidant potential against radicals of interest in dietary foodstuffs.